KERJA SAMA DALAM LEMBAGA PENDIDIKAN Analisi Tafsir Q.S. Al-Maidah:2 - Erlinawati, Erlinawati (Universitas Jabal Ghafur, 2024)
This paper aims to describe the contents of Q.S al-Maidah: 2 concerning Cooperation in Educational Institutions, and its relation to aspects of education. The research method used in this article is to use qualitative methods with the form of literature research in obtaining data. This study uses literature data sources in the form of books, journals, and other sources collected from several references related to the title of this article. The technique used in data collection is by finding a source of reform related to the discussion of this article, then analyze the contents of the data that has been collected. The results of this study show that Allah SWT in Q.S. Al-Maidah: 2 calls that it is mandatory for the believers to work together/please help their fellow in doing good and pious, and is prohibited from cooperating in carrying out exploration. Cooperation/helping to have a lot of benefits, we can respect each other between one another, and can know each other's strengths and self-deficiencies. Cooperation in educational institutions can be in the form of collaboration in providing facilities, scholarships, partnership between universities to improve the ability of students, competency tests, and talents of interest in order to improve competence and develop student creativity.Keywords: Cooperation, Educational Institution, Q.S.Al-Maidah: 2